2011
DOI: 10.1016/j.virusres.2010.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an infectious cDNA clone for Omsk hemorrhagic fever virus, and characterization of mutations in NS2A and NS5

Abstract: Omsk hemorrhagic fever virus (OHFV) is a member of the tick-borne encephalitis serocomplex of flaviviruses, and causes hemorrhagic disease in humans. In this study, an infectious cDNA of OHFV was constructed to investigate the molecular mechanisms involved in OHFV pathogenesis for the first time. Our cDNA clone was capable of producing infectious virus which is genetically identical to the parental Guriev strain, and the recombinant virus showed similar biological properties to the parental virus including gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The four amino acids identified in the present study are located in the C-terminal region of the RdRp domain. Several studies have shown that amino acid changes in the RdRp domain affect flavivirus genome replication and disease development (10,37). However, the KFK-D motif described here did not affect viral multiplication either in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The four amino acids identified in the present study are located in the C-terminal region of the RdRp domain. Several studies have shown that amino acid changes in the RdRp domain affect flavivirus genome replication and disease development (10,37). However, the KFK-D motif described here did not affect viral multiplication either in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 52%
“…Recombinant TBEV (Oshima 5-10 strain) and OHFV (Guriev strain) were recovered from infectious cDNA clones of the respective viruses (TBEV-pt and OHF-pt, respectively) as reported previously (10,11). To prepare the infectious cDNA clones of chimeric viruses ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse genetics platforms have been developed for a wide range of flaviviruses including YFV [57,58], Dengue Types 1–4 [59,60,61,62,63,64,65,66], JEV [67], Kunjin virus [68], Tick-borne encephalitis virus (TBEV) [69,70,71], Murray Valley encephalitis virus [72], Langat virus [73], West Nile virus (WNV) [6,74], and Omsk hemorrhagic fever virus [75]. Advances in the recombinant flavivirus approaches have been instrumental in new vaccine design efforts.…”
Section: Positive-strand Rna Virus Biology Reverse Genetics and mentioning
confidence: 99%
“…Previous studies have shown that NS2A protein is involved in viral assembly/release, viral RNA synthesis, regulation of NS1= expression, and inhibition of type-I interferon response (14)(15)(16)(17)(18)(19)(20). These functions are affected by amino acid substitutions within NS2A, such as NS2A-G11A, -E20A, -P30A, -T33I, -L46H, -I59N, -D73H, -R84S/A/E, -E100A, M108K, D125A, -Q187A, -K188A, -K190S, and -G200A (14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%